State-Of-The-Art and Recent Advances in Quantification for Therapeutic Follow-Up in Oncology Using PET - Carlier, Thomas; Bailly, Clément (Frontiers in Medicine, 2015)
18F-fluoro-2-deoxyglucose (18F-FDG) positron emission tomography (PET) is an important tool in oncology. Its use has greatly progressed from initial diagnosis to staging and patient monitoring. The information derived from 18F-FDG-PET allowed the development of a wide range of PET quantitative analysis techniques ranging from simple semi-quantitative methods like the standardized uptake value (SUV) to “high order metrics” that require a segmentation step and additional image processing. In this review, these methods are discussed, focusing particularly on the available methodologies that can be used in clinical trials as well as their current applications in international consensus for PET interpretation in lymphoma and solid tumors.